Physicochemical and Digestible Properties of Parboiled Black Rice With Different Amylose Contents - Zhang, Wei; Cheng, Bei; Zeng, Xuefeng; Tang, Qiuling; Shu, Zaixi; Wang, Pingping (Frontiers in Nutrition, 2022)
Black rice with different amylose contents (waxy; medium-amylose: 16.03%; high-amylose: 27.14%) were parboiled and then evaluated for physicochemical and digestible properties. The color, crystalline structure and swelling property of parboiled rice were analyzed, and the water molecular mobility, texture, and starch digestibility of cooked parboiled rice were determined. The color of black rice was only slightly changed after the parboiling treatment. The crystalline structures of waxy and medium-amylose rice were severely damaged by the parboiling treatment, while highly crystalline structure was retained in parboiled high-amylose rice. During heating in water, parboiled high-amylose rice had lower water absorption ratio and volume expansion ratio than other two varieties. After cooking, parboiled high-amylose rice had higher water molecular mobility and harder texture compared with other two varieties. Cooked parboiled high-amylose rice contained higher content of resistant starch than cooked parboiled waxy and medium-amylose rice.